Is permanent settlement an option for expatriate employees working in an international joint venture? An evaluation of Sasol’s permanent settlement policy for the United Kingdom - Wocke, Albert (University of Pretoria, 2013)
Dissertation (MBA)--University of Pretoria, 2010.